The Quintessence of Intercultural Business Communication - Moll, Melanie; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
Successful business communication is more than simply speaking your client$1 (Bs language. At the heart of all effective communication lies a fundamental understanding of human behavior. The natural result of globalization is a level of behaviors that we all share and expect. However, underneath this level are many other influencing factors. We tend to view the situation around us according to our own expectations which are often shaped by our cultural backgrounds. What happens, though, when our cultures are so different that the expectations collide? This book combines theory and practice in a way that helps you as a busy intercultural manager understand what others are communicating to you and those around you. We take apart real examples of intercultural business interaction and show you how deeply embedded cultural norms are found within a simple conversation. Then we offer you important tools and principles that you can use to improve your own intercultural business communication. After reading this book, you should have a good understanding of the basic culture types, and be able to identify most cultures based on the principles described here. Additionally, you will know which social issues, attitudes, and values appear even in the most rational business negotiation. Most importantly, your cultural awareness will help you build successful and lasting relationships with your clients across regional and global boundaries.s
The Metaculture: Our Global Culture -- Communicating Meaning -- Verbal Communication in Action -- Non-verbal Communication in Action.
Keywords: Business; Management; Personnel management; Globalization; Markets; Business and Management; Emerging Markets/Globalization.; Human Resource Management; Management; Electronic books